First evaluation of iron and manganese concentrations in coastal aquaculture water in Giao Thuy district, Nam Dinh province - Le, Nhu Da; Hoang , Thi Thu Ha; Pham, Thi Mai Huong; Duong, Thi Thuy; Nguyen, Truong Dong; Nguyen, Thi Anh Huong; Phung, Thi Xuan Binh; Nguyen, Van Phuong; Le, Thi Phuong Quynh (Vietnam Journal of Marine Science and Technology, 2021)
Aquaculture in the coastal zone has contributed significantly to economic development in Giao Thuy district, Nam Dinh province. Therefore, water quality for aquaculture plays a vital role in sustainable aquaculture production. In this paper, iron (Fe) and manganese (Mn) concentrations in aquaculture coastal water of Giao Thuy district were analyzed during the rainy season (September 2017, August 2018) and dry season at low tide. The results showed that Fe concentration varied from 0.09 mg/L (at VT5) to 2.42 mg/L (at VT4), averaging 1.12 ± 0.71 mg/L, which exceeded the critical value of the national technical regulation on marine water quality in Vietnam for coastal aquaculture water (QCVN 10:2015/BTNMT) from 1.5 times (at VT4) to 3.0 times (at VT1). Mn concentrations ranged from 0.02 mg/L (at VT9) to 0.10 mg/L (at VT1), averaging 0.05 ± 0.02 mg/L, which was lower than the critical value in the QCVN 10:2015/BTNMT. The results showed that no apparent seasonal variation was observed for both Fe and Mn concentrations. In the dry season, the Fe and Mn concentrations averaged 1.10 mg/L and 0.05 mg/L respectively, whereas they were 1.15 mg/L and 0.05 mg/L in the rainy season. The monitoring results showed that Fe was polluted in the study area and may affect aquaculture productivity. Therefore, helpful measures should be taken to minimize Fe pollution to protect water quality and develop sustainable aquaculture in Giao Thuy district, Nam Dinh province.